2019
DOI: 10.1139/cjps-2018-0276
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of four apple (Malus × domesticaBorkh.) rootstock genotypes to soil water deficits

Abstract: The use of drought-tolerant rootstocks is an important strategy in maintaining orchard productivity while meeting the increasing need to conserve water resources. The drought tolerance of two new genotypes, Vineland 1 (V.1) and Vineland 3 (V.3), was assessed along with industry standards to test the hypothesis that differences in water-use efficiency exist among these apple rootstocks. One-year-old, non-grafted nursery liners of M.9, MM.111, V.1, and V.3 were grown in a controlled-environment experiment. Plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Similarly, we found that B9, V3 and G41, which were previously reported to be more dwarfing than M26, had higher ABA content than M26 under normal conditions, and these rootstocks demonstrated better responses under osmotic stress conditions than M26. In similar studies, dwarfing rootstocks showed more drought tolerance than their vigorous counterparts, e.g., MM111 and M26 [ 51 ]. However, Jiménez et al (2013) [ 14 ] found that peach dwarfing rootstock presented a lower tolerance capacity than vigorous rootstock, suggesting that tree size is not always correlated with plant tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we found that B9, V3 and G41, which were previously reported to be more dwarfing than M26, had higher ABA content than M26 under normal conditions, and these rootstocks demonstrated better responses under osmotic stress conditions than M26. In similar studies, dwarfing rootstocks showed more drought tolerance than their vigorous counterparts, e.g., MM111 and M26 [ 51 ]. However, Jiménez et al (2013) [ 14 ] found that peach dwarfing rootstock presented a lower tolerance capacity than vigorous rootstock, suggesting that tree size is not always correlated with plant tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with Kautz et al (2015) [ 9 ] who reported a reduction in RWC in apple plants exposed to PEG and drought stresses. Leaf water potential drives several physiological, biochemical and molecular changes in stressed plants [ 21 , 50 , 51 , 52 ]. Therefore, RWC is an important indicator of plant water status and plant tolerance potential.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the impact of soil water deficit on both RILs, plants were cultivated under 75% relative soil water content (RSWC), and their biomass and metabolite profiles were assessed relative to plants cultivated under 15% RSWC (i.e., severe drought). The 15% RSWC was chosen for this study as it was previously shown to elicit severe drought stress on apple rootstocks, cotton, and red clover [ 37 , 38 , 39 ]. Plants were grown in 1.45-L high-density polyethylene (HDPE) pots (Berlin Packaging ® , Chicago, IL, USA) without drainage holes, containing two parts by volume granitic “B sand” (Hutcheson Sand & Mixes, Huntsville, ON, Canada) and 1 part peat-based potting mix (PGW, Sun Gro Horticulture Canada Ltd., Seba Beach, AB, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Investigations of transpiration response to drought stress using the gravimetric method have been conducted in a wide variety of crops, including maize ( Zea mays L.; Ryan et al., 2016), apple ( Malus pumila Mill. ; Abdelkader et al., 2022; Wright et al., 2019), and sorghum ( Sorghum bicolor L.; Ortiz et al., 2018).…”
Section: Introductionmentioning
confidence: 99%